Implementasi Program Kampung Keluarga Berencana Di Desa Boddie Kabupaten Pangke - Rachmawati, Rachmawati; Razak, Rosdianti; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the implementation of the Family Planning Village program in Boddie Village, Mandalle District, Pangkep Regency. This study used a qualitative research method with a descriptive type of research. The data collection technique used Observation, Interview and Documentation. The results of the study in conducting the analysis have four indicators, namely: (1) communication could be seen from the delivery of information and clarity of information. The socialization had run well, and was in line with expectations because the target group already understood what the implementor had explained. (2) There were two sub-resources, namely human resources and facility resources. In the implementation of the KB village program in Boddie Village, it was optimal because human resources were still unable to support the success of the KB village program, while facility resources had been able to help facilitate implementation of information to the public. (3) The disposition of the attitude of the implementor from the implementor was quite optimal because it could provide information to the public. (4) Bureaucratic structure In implementing the program, it was inseparable from the structure that has been given the task of carrying out these activities. Keywords: Implementation, Family planning village program